The impact of jurisprudential awareness on promoting social values - Majbal, Prof. Dr. Yassin Khudair Majbal; Al-Tamimi, Dr. Hanaa Mohammed Hussein Ahmed Al-Tamimi (Sulaimani Journal for Humanities, 2026)
Awareness is the path through which a person learns about things that transcend their individual self. Awareness plays a role in human survival, preserving their species, and shaping their civilization In some cases, it contributes to creating various types of difficulties, problems, conflicts, and persecution of some human beings among themselves, and sometimes it is the cause of cases of backwardness and deterioration resulting from limited awareness and conflicting visions and understandings among people.. It is the cognitive gain that we are looking for, so there was an urgent need to highlight the importance of Islamic jurisprudential awareness, as it is “the individual’s and society’s institutions’ awareness of their responsibilities in building the integrated human personality and striving to advance the process of renaissance and moral progress And the material through reforming thought, behavior and reality.” And according to psychologists: “It is the living being’s feeling of what is within himself and what surrounds him.”… The authority of values and morals is moral, and derives its authority from the value foundations upon which it is based, and from the loftiness of the aims and objectives it seeks to achieve. If noble social values prevail, societal harmony and agreement will prevail.
Keywords: jurisprudential awareness; social values; reinforcement